Martyrdom and Sacrifice in a Time of Terror - Juergensmeyer, Mark (Social research, 2008)
Mark Juergensmeyer Martyrdom and Sacrifice in a Time of Terror IN AN INTERVIEW, DR. ABDUL AZIZ RANTISI, THE POLITICAL HEAD OF the Hamas movement in Palestine, objected to my use of the term "suicide bombers" to describe his young colleagues in Hamas who chose to blow themselves up in acts of violence against Israel (Rantisi, 1998). His concern was the idea that their acts were done idiosyncratically or thoughtlessly. He preferred to think of them as "self-chosen martyrs," soldiers in a great war who diligently and reverently gave up their lives for the sake of their community and their religion. I have seen some of the videotapes taken of the young men the night before their deaths, and they indicated that these tragic foot soldiers for Hamas thought of themselves in just that way—as martyrs. They were trying not to avoid life but to fulfill it in what they considered to be an act ofboth personal and social redemption. In this way they were connecting a contempo rary political strategy to a sacred history of martyrdom and sacrifice. Though suicide bombing and self-sacrifice appear to be newly discovered devices of religious activists around the world, the idea of martyrdom has a long history within many religious traditions. Christ himselfwas a martyr, as was the founder ofthe Shiite Muslim tradition, Husain. The word martyr comes from a Greek term for "witness," such as a witness to one’s faith. In most cases martyrdom is regarded not only as a testimony to the degree of one’s commitment, but also as a performance of a religious act, specifically an act of self-sacrifice. This dimension of martyrdom links it to the activity that some scholars see as the most fundamental form of religiosity: sacrifice, a social research Vol 75 : No 2 : Summer 2008 417 rite of destruction that is found in virtually every religious tradition in the world. The term suggests that the very process of destroying is spiri tual since the word comes from the Latin, sacrificium, "to make holy." What makes sacrifice so riveting is not just that it involves killing but that it is also, in an ironic way, ennobling. The destruction is performed within a religious context that transforms the killing into something positive. Thus, like all religious images of sacrifice, martyrdom provides symbols of a violence conquered—or at least put in its place—by the larger framework of order that religious language provides. There is some evidence that ancient religious rites of sacrifice, like the destruction involved in modern-day terrorism, were perfor mances involving the murder of living beings. The later domestication of sacrifice in evolved forms of religious practice, such as the Christian ritual ofthe Eucharist, masked the fact that in most early forms of sacri fice a real animal—in some cases a human—offered its life on a sacred chopping block, an altar. In the Hebrew Bible, which is sacred to Jews, Christians, and Muslims, the book of Leviticus gives a detailed guide for preparing animals for sacrificial slaughter. The very architecture of ancient Israeli temples reflected the centrality of the sacrificial event. The Vedic Agnicayana ritual, some 3,000 years old and probably the most ancient ritual still performed today, involves the construction of an elaborate altar for sacrificial ritual, which some claim was originally a human sacrifice (Staal, 1983). This was most likely so at the other side of the world at the time of the ancient Aztec empire, when conquered soldiers were treated royally in preparation for their role in the sacri ficial rite. Then they were set upon with knives. Their still-beating hearts were ripped from their chests and offered to Huitzilopochtli and other gods, eventually to be eaten by the faithful, and their faces were skinned to make ritual masks. Why are such gory acts ofsacrifice central to religion? The attempt to find answers to that question has been a preoccupation of scholars for over a century. The insights of such pioneering thinkers as Émile Durkheim and Sigmund Freud have been revived by recent scholars, including Maurice Bloch, René Girard, Walter Burkhert, and Eli Sagan, 418 social research who give social and psychological...